Pengaruh Model Snowball Throwing Dan Minat Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Sekolah Dasar - Masria, Ali (Jurnal Didaktika Pendidikan Dasar, 2021)
The purpose of this study was to see the difference in the influence of the Snowball Throwing model, conventional models and students' interest in learning on learning outcomes. This type of research is a quasi-experimental research using a quantitative approach. The population was all fourth grade students of the Gugus III Public Elementary School, Lembah Melintang District, while the sample consisted of 42 grade IV students at the 02 Lembah Melintang Elementary School. 21 students in the experimental class and 21 students in the control class. Data from research results obtained from student learning outcomes tests. The ratio of X1 and X2 to Y is 16.25%, while the percentage ratio of X2 a and X2 b to Y is 16.82%. The results show that there is an influence of the Snowball Throwing model and interest in learning outcomes of Social Sciences in class IV Elementary School 02 Lembah Melintang.